Comparison of Hand Grip Strength Between Vitamin- D Supplemented and Non- Supplemented Hypothyroid Patients.: Life Sciences-Physiology - Kumari. N, Ratna; Vijayalakshmi; Prema, G.S.; Panda, S.; Ibrahim (International Journal of Life Science and Pharma Research, 2022)
Vitamin- D deficiency is one of the causes for muscle disorders. The present study was aimed to evaluate the performance of hand grip muscle strength (HGS) to determine muscle dysfunctions in patients with newly diagnosed hypothyroidism. Our study objectives are to compare the hand grip strength (HGS) results with vit-D supplement and without vit-D after 8 months’ of thyroid therapy. A prospective study of Eight months’ period was carried out among 120 subjects attending the Shadan hospital in India. About 40 controls were healthy individuals, 80 subjects were newly diagnosed hypothyroid cases, hypothyroid were divided into two equal groups, Age and gender-matched subjects diagnosed as hypothyroid were included. The three study groups were divided: Group1-. Vitamin-D supplemented cases, Group-2 without Vitamin-D supplementation cases, Group-3 healthy controls. TSH, T3 and T4 levels were estimated by using the immunoassay method. Hand grip strength (HGS) assessed by hand grip dynamometer and Vitamin-D levels were assessed by Minividaas. Statistical analysis was done with sigma plot 14.5 version. Between Hypothyroid groups, supplemented and non-supplemented, statistical significance was obtained for reduced BMI, improved levels of Vitamin-D, reduction of TSH, not much change in T3&T4, and improved HGS. Statistically significant HGS was seen with high levels TSH, low T3&T4. HGS in left &right hand Standard mean is 19.6 & 27.6 and 15.6 & 24.56 respectively. HGS was found to be improved with Vitamin-D supplementation in hypothyroid cases along with hypothyroid treatment. We found that Vitamin-D deficiency is one of the reasons to decrease HGS in hypothyroid patients, Vitamin-D supplementation improves handgrip muscle strength, which is the major concern in hypothyroidism. Our study concludes Vitamin-D supplementation is beneficial in hypothyroid patients who have decreased HGS.